Impact of an Educational Intervention on Dengue Health Literacy among Secondary School Students in Budhiganga Rural Municipality - Parajuli, Surya Bahadur; Yadav, Binod Kumar; KC, Heera; Mishra, Anjali; Khan, Sajjad Ahmed (Journal of College of Medical Sciences-Nepal, 2025)
Background Dengue fever remains a significant public health issue due to insufficient awareness and preventive measures. Secondary school students can serve as key agents in promoting prevention and disseminating information within communities. This study aimed to assess the impact of an educational intervention on dengue health literacy among secondary school students. Methods A pre-post intervention study was conducted among 104 secondary school students in Budhiganga Rural Municipality, Morang, Nepal, from January 2024 to February 2024. Ethical clearance was obtained from the Institutional Review Committee (Ref: IRC-PA-361/2023). A structured questionnaire assessing dengue health literacy was administered before and immediately after the intervention. Statistical analysis was performed using a paired t-test, considering a p-value of <0.05 as statistically significant. Results The mean±SD age of participants was 14.89±0.93 years, with 59 (56.7%) being male. The pre-intervention mean dengue health literacy score was 11.34 ± 3.77, which increased to 15.45 ± 3.75 post-intervention. The improvement was statistically significant (p < 0.001), demonstrating the intervention’s effectiveness. Conclusions The educational intervention significantly improved dengue health literacy among secondary school students, highlighting the potential of school-based health education programs.